Engaging L2 Learners: Exploring Teachers’ Perceptions of Vocabulary Cards - Puspitasari, Natalia; Kurniawati, Lemmuela Alvita (Universitas Muhammadiyah Barru, 2025)
This study examines two primary aspects: the extent to which teachers utilize vocabulary cards to enhance L2 learners' speaking skills and how teachers perceive the use of vocabulary cards for this purpose. Involving three English teachers at a private English course in Yogyakarta, Indonesia, this study employed a qualitative research method that included interviews and observations. The teacher participants were selected based on their use of vocabulary cards as instructional media and their willingness to be involved in this study. The observations were conducted for two consecutive days, and the data were collected from the interview results, with the observation notes coded and generated into some themes. The study found that teachers employ vocabulary cards to help students understand new materials and improve their speaking skills. Teachers perceive vocabulary cards as making learning more enjoyable and significantly increasing students' vocabulary repertoire. Several implications arise from this study. Vocabulary cards can enhance L2 students' speaking abilities by making new material more understandable. Teachers positively perceive vocabulary cards as they create a more engaging learning environment and enrich students' vocabulary more effectively. Future research should investigate the effectiveness of vocabulary cards across various levels of English proficiency to determine their impact on learners at different stages of language development. Additionally, using other data collection techniques, such as questionnaires and surveys, could provide a more comprehensive understanding of their effectiveness in diverse learning contexts.